A POTENTIOMETRIC STUDY OF THE STABILITY OF AQUEOUS YTTRIUM-ACETATE COMPLEXES FROM 25 TO 175 °C AND 1-1000 BAR - Tagirov B.; Schott J.; Zotov A.; Koroleva L.; Suleimenov O. (My University, 2007)
The stability of yttrium–acetate (Y–Ac) complexes in aqueous solution was determined potentiometrically at temperatures 25–175 °C (at Ps) and pressures 1–1000 bar (at 25 and 75 °C). Measurements were performed using glass H+-selective electrodes in potentiometric cells with a liquid junction. The species YAc2+ and were found to dominate yttrium aqueous speciation in experimental solutions at 25–100 °C (log [Ac−] < −1.5, pH < 5.2), whereas at 125, 150 and 175 °C introduction of into the Y–Ac speciation model was necessary. The overall stability constants βn were determined for the reactionwhere terms in square parentheses stand for the molal concentrations [mol/kg H2O], and γi is the activity coefficient of the ith species. With temperature increase from 25 to 200 °C, the values of log β1, log β2 and log β3 increase from 2.27 to 4.51, 3.86 to 7.86 and 4.63 to 10.24, respectively. Increase of pressure results in decrease of the stability of all three complexes: log β1 decreases by 0.21 and 0.37, log β2 by 0.40 and 0.73, and log β3 by 0.57 and 1.01 when pressure increases from 1 to 1000 bar at 25 and 200 °C, respectively. However, the effect of pressure on Y speciation is much less pronounced than that of temperature and results only in a decrease of the predominance field of in high-pressure solutions. The calculated values of the partial molal thermodynamic functions for the overall formation reactions are: ΔrS∘ = 23.4, 42.5, and 54.5 cal/mol K, , 122.2, and 182.5 cal/mol K, and ΔrV∘ = 16.1, 30.9, 44.3 cm3/mol for YAc2+, and , respectively. The revised Helgeson–Kirkham–Flowers (HKF) equation of state parameters were generated for Y–Ac complexes.